PRIBADI SEHAT: PERSPEKTIF KONSELING DAN ALQURAN - Thalib, Thalib (Hunafa: Jurnal Studia Islamika, 2008)
In  psychological point of view, whatever occurs in an adult is influenced by his or her life condition in his or her adulthood, particularly in the first years of his or her age. The offspring and milieu give a major influence to the formation of  attitude and of behavior of a child. A child’s personality will be positive whenever he is in a healthful family and social milieu. It is the two that form the healthful personality of the child. The healthful personality, in psychological point of view, is one that can manage himself, others and his milieu. Healthful personality in relation to oneself, possesses ten characteristics; that in relation to other people, possesses two characteristics; This article deals the comparison between  healthful personality from the view of psychology and that of the Qur’an.Kata Kunci:  pribadi sehat, konsep konseling, konsep Alquran